Dimerisation of the Drosophila odorant coreceptor Orco - Mukunda, Latha; Lavista-Llanos, Sofia; Hansson, Bill S.; Wicher, Dieter (Frontiers in Cellular Neuroscience, 2014)
Odorant receptors (ORs) detect volatile molecules and transform this external information into an intracellular signal. Insect ORs are heteromers composed of two seven transmembrane proteins, an odor-specific OrX and a coreceptor (Orco) protein. These ORs form ligand gated cation channels that conduct also calcium. The sensitivity of the ORs is regulated by intracellular signaling cascades. Heterologously expressed Orco proteins form also non-selective cation channels that cannot be activated by odors but by synthetic agonists such as VUAA1. The stoichiometry of OR or Orco channels is unknown. In this study we engineered the simplest oligomeric construct, the Orco dimer (Orco di) and investigated its functional properties. Two Orco proteins were coupled via a 1-transmembrane protein to grant for proper orientation of both parts. The Orco di construct and Orco wild type proteins were stably expressed in CHO (Chinese Hamster Ovary) cells. Their functional properties were investigated and compared by performing calcium imaging and patch clamp experiments. With calcium imaging experiments using allosteric agonist VUAA1 we demonstrate that the Orco di construct - similar to Orco wt - forms functional calcium conducting ion channel. This was supported by patch clamp experiments. The function of Orco di was seen to be modulated by CaM in a similar manner as the function of Orco wt. In addition, Orco di interacts with the OrX protein, Or22a. The properties of this complex are comparable to Or22a/Orco wt couples. Taken together, the properties of the Orco di construct are similar to those of channels formed by Orco wt proteins. Our results are thus compatible with the view that Orco wt channels are dimeric assemblies.